Penguatan Ekonomi Kerakyatan Berlandaskan Pancasila: Tinjauan Kebijakan Kemenko Perekonomian: Strengthening the People's Economy Based on Pancasila: Policy Review of the Coordinating Ministry for the Economy - Devi Okta Viantri; Firly Aulia Berliani; Muhammad Fajrul Nizam; Zahratul Jannah (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
The people's economy is an economic model that positions the people as both subjects and objects of development, based on the values of mutual cooperation and togetherness as reflected in Pancasila. This study aims to analyze the role and policies of the Coordinating Ministry for Economic Affairs in strengthening the people's economy based on Pancasila. The research method uses a qualitative approach with literature study of various policy documents and official reports. The results show that the Coordinating Ministry for Economic Affairs has coordinated various strategic policies such as facilitation of People's Business Credit (KUR), development of entrepreneurial ecosystems, and integration of MSMEs with the digital economy. The implementation of these policies still faces challenges such as disparities in regional capacity and cross-sectoral coordination. This article concludes that the internalization of Pancasila values in people's economic policies is evident, but strengthening synergy across ministries/agencies is needed to ensure the policy benefits are truly felt by all layers of society.